DEVELOPMENT ISSUES, PROBLEMS AND TRENDS IN THE DEVELOPMENT OF UZBEK TELEVISION - Rakhmatullaeva, Ilmira (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2023)
This article evolutionarily studied the process of forming television in Uzbekistan. According to historical experience, the inclusion of a new, previously absent media in the system has always been an advanced step in terms of the efficiency of the transfer of socially significant data and its technical development. However, the new medium of mass communication, especially at the initial stage of its development, cannot demonstrate its capabilities and methods characteristic of nature. At the beginning of the 20th century, when radio began its steps, as well as the use of "newspaper forms" of presentation of material, television relied on the experience of radio as a new means of communication that performs social tasks. In the media system of the former USSR, television went a long way before in its early years it became a means of state propaganda, which aroused public admiration as an attractive technical means. The article explores the modern media space of national television, which arose in the middle of the 20th century, the modern system of mass communications, as well as the peculiarities of the formation and functioning in the context of the political life of society. The programs of Uzbek television by genre character were also investigated, the best projects in the history of television were analyzed. The spiritual and ethical aspects of the development of new genres and formats of television, as well as their specific influence on the audience, have been studied.
Keywords: television; art; public; mass media; ideology; television journalism; video informant; radio; television club; presenter